Shadowless Projection Mapping using Retrotransmissive Optics - Hiratani, Kosuke (IEEE transactions on visualization and computer graphics, 2023)
This paper presents a shadowless projection mapping system for interactive applications in which a target surface is frequently occluded from a projector with a user's body. We propose a delay-free optical solution for this critical problem. Specifically, as the primary technical contribution, we apply a large format retrotransmissive plate to project images onto the target surface from wide viewing angles. We also tackle technical issues unique to the proposed shadowless principle. First, the retrotransmissive optics inevitably suffer from stray light, which leads to significant contrast degradation of the projected result. We propose to block the stray light by covering the retrotransmissive plate with a spatial mask. Because the mask reduces not only the stray light but the achievable luminance of the projected result, we develop a computational algorithm that determines the shape of the mask to balance the image quality. Second, we propose a touch sensing technique by leveraging the optically bidirectional property of the retrotransmissive plate to support interaction between the user and the projected contents on the target object. We implement a proof-of-concept prototype and validate the above-mentioned techniques through experiments